Web tools for long term strength data processing - Breslavsky, D. V.; Breslavska, O. O.; Kozlyuk, A. V. (NTU "KhPI", 2016)
The paper concerns the questions of development the specialized web-based software for processing of the long term strength data. The goal is to develop the web tools which could fill up the gap between high theoretical background in Continuum Damage Mechanics and insufficient knowledge about the experimental data by way of storage them and processing the values of constants. The approach for storing of the experimental physical and mechanical properties for different temperatures is described. The structure of database as well as the interface section for selection of different data sets, which include the fracture stress values with appropriate values of time, are presented. Selected fields of database are used for deriving the constants for damage kinetic equations. Two algorithms of deriving are discussed, the first was designed for constant temperature conditions as well as the second assigns for definite interval of temperatures. The numbers of experimental data sets for each algorithm are determined. The example of the deriving process for nickel based alloy is presented and plots of time dependencies for damage parameter are built. The discussed software is designed for engineers and research associates who are working in area of modeling of high temperature properties in materials and structural elements.

В статті розглянуто питання розробки спеціалізованого програмного забезпечення для обробки даних з довготривалої міцності. Описано підхід, застосований для зберігання даних, та представлено опис інтерфейсу, що застосовується при цьому. Обговорено два алгоритми з отримання констант для кінетичного рівняння для параметру пошкоджуваності, перший з яких розроблено для умов постійної температури, а другий - для визначеного інтервалу температур. Наведено приклад опису процесу отримання значень констант для жароміцного нікелевого сплаву. Програмне забезпечення, що обговорюється, призначено для інженерів та наукових співробітників, які працюють у напрямку моделювання високотемпературних властивостей матеріалів та елементів конструкцій.
Web-інструменти для обробки даних щодо довготривалої міцності
Keywords: creep; long term strength; experimental results; web-application; material data storing; kinetic damage equation; scalar damage parameter; повзучість; довготривала міцність; експериментальні дані; зберігання даних про матеріали; скалярний параметр пошкоджуваності